The Problems, Issues and Challenges of Planning Education in Indonesia - Mochtarram Karyoedi (Journal of Regional and City Planning, 1996)
This  article  is  intended  to  describe  the  current  development  of  planning  education  in Indonesia and will consist of 3 main issues as follows: Firstly,  a quick look at the dynamic of  national,  regional  and  local  planning  development  concept  and  practice,  and  in  line with the need of Indonesian development program this paper is also intended to explore the importance  and  need  of  planning  education,  and lastly this paper is going to discuss the development of planning education in Indonesia.